South African anti-apartheid documentaries 1977-1987: some theoretical excursions - Steenveld, Lynette Noreen (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 1991)
This study examines anti-apartheid documentary production in South Africa between 1977 and 1987. These documentaries were produced by a variety of producers in order to record aspects of South Africa's contemporary social history, and as a means of contributing - in some way - to changing the conditions described. While the 'content' of the documentaries is historical and social, and their intention political, this study is aimed at elucidating how a documentary, as a representational system, produces meaning. The study is therefore located within the discourse of film studies. My study is based on the theory that a documentary is the embodiment of several relationships: the relationship between social reality and documentary producers; the social relationships engaged in, in the production of the text; the relationship between the text and its audience 1, and the relationship between the audience and its social context. This informs my methodological approach in which analysis appropriate to each area of study is used. Using secondary sources obtained through standard library research, I pursue social and historical analysis of the 1970s and 1980s in order to contextualise both the producers of the documentaries, and their audience. The social relations of production of a text are examined using material gathered through extensive interviews with the producers and published secondary material. How this impinges on the documentary is ascertained through detailed textual analysis of 30 documentaries. For analytical clarity each chapter focuses on a specific aspect of documentary - although I do show how the various relationships impinge on each other. This research finds that the documentaries faithfully reflect the anti-apartheid ideology dominant in the extra-parliamentary opposition in the period under discussion - to the extent that all forms of consciousness are framed by this discourse. An examination of the textual strategies used shows that they are bound by the conventions of broadcast television. They therefore construct a spectator-text relationship which is not consistent with the political concern that democratic relationships be established as the basis of a post-apartheid society. In other words, there is an inconsistency between the ideology espoused, and the way in which film- and videomakers, in their specialised field of production, practise their politics. This can be attributed to the over-riding political intention of the documentarists 'to record' what is happening, and to establish a popular archive which can be used by extra-parliamentary opposition groups in their struggle against apartheid.
Keywords: Documentary films -- South Africa -- History and criticism; Apartheid -- South Africa; Anti-apartheid movements -- South Africa